Cultural Challenges and Countermeasures in the Construction of Campus Culture in Colleges and Universities - Jinying Qiu , Lin Li , Siyu Zhai (Forest Chemicals Review, 1970)
Culture is the blood of a nation and the spiritual home of the people. Since the rise of the construction of campus culture in colleges and universities in the mid-1980s, scholars have done a lot of theoretical research on the construction of campus culture in colleges and universities. The leaders in them have initiated a lot of fruitful reforms and practice on the construction of campus culture. College teachers and undergraduates, as the main body of campus culture, actively participate in the construction of campus culture, making China’s campus culture present a situation of sustained, healthy and flourishing development. Especially in the 1990s, after the establishment of the socialist market economic system, the campus culture of colleges and universities reflects and disseminates various cultural phenomena, cultural achievements and cultural spirit, relying on colleges and universities. Through the material environment, system construction and the spirit of colleges and universities, every member living in them has a subtle understanding and recognition of advanced culture in terms of ideology, psychological adjustment, behavior criterion and value orientation, thus shaping people’s characters, spirit and beliefs, and highlighting the core competitiveness and spirit of colleges and universities. Through a brief review of the campus culture construction in colleges and universities since its rise, this paper throws light on the connotation of campus culture in colleges and universities, and reveals the cultural challenges faced by the campus culture in colleges and universities, including the integration of modern culture and traditional culture, the collision between Western culture and Chinese Culture, and the revolution from traditional cultural transmission mode to modern transmission mode. And this paper also discusses the countermeasures to the construction of campus culture from the perspective of culture, including critically assimilating and inheriting traditional culture, developing and innovating modern culture. And we should critically learn from Western social and cultural values and promote the construction of the core socialist value system. This paper also emphasizes campus culture in colleges and universities should be rooted in the soil of network culture and the advanced socialist culture should be transmitted with the times.